2021
DOI: 10.21203/rs.3.rs-589244/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trypanosoma Cruzi Affects The Sensory Biology of Triatoma Dimidiata (Hemiptera: Reduviidae).

Abstract: Background: Triatoma dimidiata is a vector of the protozoan parasite Trypanosoma cruzi, the etiologic agent of Chagas disease. Phenotypic plasticity allows an organism to adjust its phenotype in response to stimuli or environmental conditions. Understanding the effect of T. cruzi on the phenotypic plasticity of its vectors, known as triatomines, has attracted great interest because of the implications of the parasite-triatomine interactions in the eco-epidemiology and transmission of the parasite. We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Trypanosoma cruzi can also affect sexual dimorphism, due to hormones that may serve as communication signals (Alavez-Rosas et al, 2023) as reported by May-Concha et al (2021), who studied the infection of T. cruzi in Triatoma dimidiata Latreille (Hemiptera: Reduviidae: Triatominae), and when measuring the antennae sensilla, they reported that infected insects have a greater perception of contact stimuli and olfactory perception than uninfected insects, which favors vectorial transmission of the parasite.…”
Section: Introductionmentioning
confidence: 87%
“…Trypanosoma cruzi can also affect sexual dimorphism, due to hormones that may serve as communication signals (Alavez-Rosas et al, 2023) as reported by May-Concha et al (2021), who studied the infection of T. cruzi in Triatoma dimidiata Latreille (Hemiptera: Reduviidae: Triatominae), and when measuring the antennae sensilla, they reported that infected insects have a greater perception of contact stimuli and olfactory perception than uninfected insects, which favors vectorial transmission of the parasite.…”
Section: Introductionmentioning
confidence: 87%
“…For example, the aggregation and geotaxis of males and females of T. infestans , have been analysed, and authors concluded that infected bugs reinforced their gregariousness [ 29 ]. Additionally, it has been observed significant differences between sensilla patterns of infected and non-infected insects have been observed [ 30 ]. More direct evidence of possible parasite-driven effects indicated that infected bugs were more active and likely to detect human odour than non-infected bugs [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the aggregation and geotaxis of males and females of T. infestans, have been analyzed, and determined that infected bugs reinforced their gregariousness 29 . In terms of the morphology that is related to the chemical ecology, it has been found signi cant differences between sensilla patterns of infected and noninfected insects from sylvatic and domestic habitats 30 . More direct evidence of manipulation indicated that infected bugs were more active and likely to detect human odour than non-infected animals 31 .…”
Section: Introductionmentioning
confidence: 99%